Finance and Development, March 2011. (Finance and Development; Finance and Development ;, 2012)
Latin America: An End to Boom and Bust? covers prospects in that region, which has managed to sustain a decade of prosperity after a history of boom and bust cycles. In our cover story, Nicolas Eyzaguirre, Director of the IMF's Western Hemisphere Department, says Latin America has the potential to become an increasingly important global player. But boosting productivity and competitiveness remain key policy challenges and the fruits of success must be more broadly shared. Other articles on our cover theme look at the prospects for Brazil, inequality in Latin America, and how to raise productivity. Turning from Latin America, we interview former IMF Managing Director Michel Camdessus, former IMF MD and now head of a group of luminaries tasked with generating ideas on how to make the global monetary system more stable in the wake of the world financial crisis. This issue of F and D also features articles on financial market cycles, public investment in infrastructure, whether to worry about inflation or deflation, democracy and liberalization, how to manage health care spending, and rising food prices. People in Economics profiles growth guru Robert Solow, winner of the 1987 Nobel Prize in economics. Our regular Back to Basics feature explains financial services. Data Spotlight looks at how access to financial services is growing in developing countries; and Picture This highlights the IMF's new database of public debt since 1880.